Traits or habitat? Disentangling predictors of leaf‐litter decomposition in Amazonian soils and streams. Issue 4 (9th April 2019) - Four, B.; Cárdenas, R. E.; Dangles, O.
Abstract: Quantifying the relative contributions of plant physicochemical traits and environmental conditions to leaf decomposition is essential to increase our understanding of ecosystem processes in forested terrestrial and aquatic habitats. This is particularly crucial in tropical rainforests that display high levels of tree diversity and environmental heterogeneity over relatively small spatial scales. For example, in Amazonia, detritus from hundreds of tree species fuels carbon cycling in watersheds, but much remains to be learned about how species traits interact with environmental conditions to mediate decomposition. We investigated the leaf‐litter decomposition of 17 tree species with contrasting traits in soil and stream habitats in Yasuní National Park, Ecuador. We hypothesized that (1) habitat type would be the major determinant of leaf decomposition (faster in stream than soil systems), (2) species would be ranked similarly in terms of leaf decomposition rates, according to decomposability traits (i.e., litter quality), within each habitat, and (3) the variability of leaf decomposition within habitats would be greater for soil than for stream systems. Contrary to our first hypothesis, we found that leaf‐litter decomposition rates for any given tree species were similar in stream and soil systems. However, we found that the relative importance of litter traits for decomposition such as concentrations of micronutrients (Mn and Cu, in particular) was consistent across habitats. Finally, we found that decomposition was equally highly variable in both terrestrial and aquatic systems. This variability was explained by differences in microhabitat within soils, but appeared to be more stochastic in streams. Overall, we found that plant traits had an overwhelming effect on the decomposition process in the intertwined aquatic and terrestrial matrices of the Yasuní rainforest, with significant effects of microhabitat features. This study sheds light on the fate of the pool of dead organic matter in tropical rainforests and highlights the need for further studies of the mechanisms underlying microhabitat variability.